2007
DOI: 10.1262/jrd.19047
|View full text |Cite
|
Sign up to set email alerts
|

Species-Related Differences in the Mechanism of Apoptosis During Structural Luteolysis

Abstract: Abstract. Luteolysis is defined as the loss of function and subsequent involution of the luteal structure. The luteolytic process is usually subdivided, whereby the decline in progesterone is described as functional luteolysis and the structural involution is described as structural luteolysis. After the corpus luteum ceases to produce progesterone, it decreases in size, experiences a loss of cellular integrity, and then disappears from the ovary as a result of apoptosis of luteal cells. However, the control m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
86
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 75 publications
(90 citation statements)
references
References 71 publications
3
86
1
Order By: Relevance
“…Luteolysis is defined as the loss of function and subsequent involution of the luteal structure. The luteolytic process is usually subdivided, whereby the decline in progesterone is described as functional luteolysis and the structural involution is described as structural luteolysis (Sugino and Okuda, 2007). Apoptosis plays a key role in the demise of the majority of mammalian gonadal cells (follicular granulosa and luteal cells in ovaries and germ cells in the testes) during the reproductive cycle.…”
Section: Discussionmentioning
confidence: 99%
“…Luteolysis is defined as the loss of function and subsequent involution of the luteal structure. The luteolytic process is usually subdivided, whereby the decline in progesterone is described as functional luteolysis and the structural involution is described as structural luteolysis (Sugino and Okuda, 2007). Apoptosis plays a key role in the demise of the majority of mammalian gonadal cells (follicular granulosa and luteal cells in ovaries and germ cells in the testes) during the reproductive cycle.…”
Section: Discussionmentioning
confidence: 99%
“…Inter-species differences in the factors that induce luteal cell apoptosis and the low number of apoptotic cells observed in situ at any given time has made clarification of the precise mechanisms involved challenging (reviewed in Sugino & Okuda (2007)). In an attempt to overcome this latter problem, Goyeneche et al (2006) used an in vitro model of rat luteal cell apoptosis to investigate the cellular machinery involved.…”
Section: Bh3 Interacting Domain Death Agonistmentioning
confidence: 99%
“…Previous studies have demonstrated that PRL shows specific roles in ovarian function, such as its luteotropic effect on newly formed corpora lutea [6] and luteolytic effect on aged corpora lutea in rats [30]. A PRL surge occurs during the periovulatory period [1,29,31,32] and induces apoptosis of lutein cells and structural luteolysis when the corpus luteum ceases progesterone production in rats [4,6,8,15,30].…”
mentioning
confidence: 99%